Silicon (100) electrodes resistant to oxidation in aqueous solutions: An unexpected benefit of surface acetylene moieties - Ciampi, Simone; Eggers, P.; Le Saux, G.; James, M.; Harper, J.; Gooding, J. (American Chemical Society, 2009)
Here we report on the functionalization of alkyne-terminated alkyl monolayers on highly doped Si(100) using "click" reactions to immobilize ferrocene derivatives. The reaction of hydrogen-terminated silicon surfaces with a diyne species was shown to afford very robust functional surfaces where the oxidation of the underlying substrate was negligible. Detailed characterization using X-ray photoelectron spectroscopy, X-ray reflectometry, and cyclic voltammetry demonstrated that the surface acetylenes had reacted in moderate yield to give surfaces exposing ferrocene moieties. Upon extensive exposure of the redox-active architecture to oxidative environments during preparative and characterization steps, no evidence of SiOx contaminants was shown for derivatized SAMs prepared from single-component 1,8-nonadiyne, fully acetylenylated, monolayers. An analysis of the redox behavior of the prepared Si(100) electrodes based on relevant parameters such as peak splitting and position and shape of the reduction/oxidation waves depicted a well-behaved redox architecture whose spectroscopic and electrochemical properties were not significantly altered even after prolonged cycling in aqueous media between -100 and 800 mV versus AglAgCl. The reported strategy represents an experimentally simple approach for the preparation of silicon-based electrodes where, in addition to close-to-ideal redox behavior, remarkable electrode stability can be achieved. Both the presence of a distal alkyne moiety and temperatures of formation above 100 °C were required to achieve this surface stabilization. © Copyright 2009 American Chemical Society.